Implementation of a Novel MPPT Tactic for PV System Applications on MATLAB/Simulink and Proteus-Based Arduino Board Environments - Abdelkhalek Chellakhi; Said El Beid; Younes Abouelmahjoub (International Journal of Photoenergy)
This paper is aimed at harvesting the photovoltaic systems extracting power under difficult irradiance and load conditions, by proposing a novel maximum power point tracking (MPPT). This proposed MPPT tactic has been examined under various climatic and load conditions using two powerful and accurate simulation environments for PV systems, MATLAB/Simulink and Proteus. The first implementation using the MATLAB/Simulink software was carried out to examine the performance of the novel MPPT tactic under sudden insolation and load change, where the second implementation using the Proteus software was carried out in order to prove that the novel MPPT tactic can be easily implemented using low-cost components, Arduino board, and LCD display. The simulation results prove that the novel MPPT tactic has a high convergence speed to locate the MPP, especially at fast solar irradiation and load variation with zero oscillation under steady-state operation, which takes less than 9.6 milliseconds (ms) under the MATLAB/Simulink software and 0.24 microseconds (μs) under Proteus environment. That means it is about six times faster than P&O and five times faster than INC MPPT methods, and its tracking efficiency is between 99.40% and 99.86%. Furthermore, the novel MPPT tactic shows the best tracking accuracy and better ability to mitigate power losses under overall simulation scenarios compared with other traditional MPPT methods.